Vivência dos trabalhadores da construção civil no contexto da gestão público-privado e os impactos para sua saúde - Borges, Elisa Silva (Universidade Federal de São Carlos, 2012)
In this dissertation, it was possible to contribute to the discussion on the health of workers in the area of construction, housing projects promoted by the partnership between public and private bodies. Despite being an important sector for the Brazilian economy, the literature is scarce, especially in psychology, studies on how workers experience the impacts of the conditions and labor relations, offered by the managers on their health. Based on theoretical and methodological framework of Social Epidemiology, the psychodynamics of work and ergonomics of the authors, this work was to study how the servants and builders of a housing project in a municipality of São Paulo, experienced the relations and conditions work offered by local organization partnerships, business and Caixa Econômica Federal. To this end, we identified the different roles of the implementing partners of the works; known relations and working conditions, rates of illness and related benefits were raised. Information was obtained through questionnaires, interviews, direct observations, archival research and analyzed by means of triangulation and the subsequent definition of categories, built from examination of consensus and disagreements identified in the content of the speeches. The results showed that the work funded by the Pro-House was marked by the logic of capital, which led to poor conditions and labor relations. Workers who accompanied the insertion of the master builder, first as a facilitator of communication with managers and, secondly, as loss of control over small decisions made by the collective. The qualification, even if not provided by the managers, through courses, when the organization of work allowed, workers develop new skills. Security measures at work were palliative, but the workers were used on defensive strategies and mobilization, which differed according to the employment relationship. However, some workers became ill or resigned because they could not always overcome the organization of work.
Experience of construction workers in the context of public-private management and impacts to your health.
Keywords: Psicologia social; Construção civil; Trabalho; Saúde; CIENCIAS HUMANAS::PSICOLOGIA